The association of prolactin gene polymorphism with egg production traits in Alabio and Mojosari ducks - I. Damayanti; S. Sudaryati; D. Maharani (Diponegoro University, 2022)
Prolactin (PRL) affects egg production in duck as it induces broodiness and promotes follicles development. The objective of this study was to investigate the association between polymorphism of PRL gene and egg production traits in Alabio and Mojosari Ducks. Genomic DNA were isolated from 111 blood samples (51 Alabio and 60 Mojosari). PCR and sequencing were performed to identify poly-morphisms and genotype of the animals. Data recording of the ducks including body weight at 16 weeks of age and at first egg, average weight of three first eggs laid and egg number laid up to 3, 6 and 12 months production were collected. Data were analyzed using independent sample t-Test. As a result, two single nucleotide polymorphisms (SNP) were detected in intron 4. Both SNP C-5796A and SNP T-5817C were found to have association with egg number laid up to three months (P<0,005). The CA/TC genotype had higher egg number than CC/TT. These suggested that SNP C-5796A and SNP T-5817C could be potential markers for marker assisted selection to increase egg number in duck.